Social implications for low emissions dairy in Kenya: Exploring opportunities for youth - International Livestock Research Institute (International Livestock Research Institute, 2020)
Research by ILRI and partners is helping to better understand the implications of dairy intensification and the potential for youth employment in agriculture. The research is intended to address the critical need to reduce youth unemployment and greenhouse gas emissions in Africa.